Changements socio-environnementaux et dynamiques des paysages ruraux le long du gradient bioclimatique nord-sud dans le sud-ouest du Niger (régions de Tillabery et de Dosso) - José Luis San Emeterio; Frédéric Alexandre; Julien Andrieu; Alain Génin; Catherine Mering (VertigO)
This article analyzes the changes which have occurred in land occupation and vegetation cover over the past few decades in a number of villages scattered along the bioclimatic gradient in the South-West of Niger, from the Tillabéry-Filingué line in the North to Gaya (on the Niger-Benin border) in the South. Diachronic analyses were performed based on satellite photographs (CORONA March and October 1965) or aerial photographs (IGN mission in March 1975) which were compared to current Google Earth photographs. These analyses were then confronted to interviews conducted in the various villages as well as to surveys of the state of the vegetation. If researchers emphasize the resumption of rainfall since the mid-1990s, they also show that the South-West of Niger paradoxically presents an increased socio-environmental vulnerability. It seems possible to generalize this observation at the scale of the two regions. However, the research undertaken here leads to a more nuanced conclusion : when data are disaggregated, the situation looks very diversified, revealing, independently from the bioclimatic gradient and from the meridian differentiation linked with the fossile valleys (dallols), situations where the vulnerability of both populations and ecosystems appears more or less pronounced.